Handbook of unethical work behavior : implications for individual well-being (New York : M.E Sharpe, 2013)
This handbook covers the widest possible range of organizational misbehaviors (age, race, and gender discrimination, abuse, bullying, aggression, violence, fraud and corruption), all with an eye toward the effects on individual and organizational health and well-being. It is the first-ever single-source resource on this important topic
Part 1. Attacking Others: Revenge, Aggression, Bullying and Abuse -- Part 2. Harmful Behaviors and Work Stress -- Part 3. Individual Differences, Justice and Moral Function -- Part 4. Organizational and Societal Perspective .
Includes bibliographical references and index.
Keywords: LEADERSHIP ASPECT; POLITICAL SCIENCE; HARRASSMENT